ARQUITETURA ESCOLAR MODERNA: ANÁLISE DO CENTRO EDUCACIONAL DE PESQUISA APLICADA EM MACEIÓ AL - Lima, Jéssica; Silva, Camila; Torres, Leila; Cavalcante, Morgana; Ferreira, Dilson (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The concept of "escola parque", idealized by Anísio Teixeira, consists of an ambitious project of reformulation of the planned education to become a national model at national level both in its pedagogical profile and in its physical viability, becoming in an important modernist landmark. Following this pattern, the Applied Educational Research Complex (CEPA) emerged in 1958 in the city of Maceió, becoming a school in Alagoas, and has long been considered the largest educational contingent in Latin America. In this context, the present work had as objective to make a study of modern school architecture, and an analysis of the design strategies adopted in this Complex. The research was based on qualitative techniques, through theoretical foundation and case study, technical visit, photographic survey and design analysis, realized in the State School Maria Jose Loureiro and Moreira e Silva School, components of the Complex. Throughout the analysis, it was realized that the Complex consists of a Strong example of the Modern Movement in Architecture, with the presence of architectural elements intrinsic to this style, as well as the concepts of sport inherent in the model of "escola parque". Understanding this way, its importance, still today, for the state of Alagoas.